Effectiveness Of Fibrinolytic Therapy in ST-Elevation Myocardial Infarction Patient in Archipelago Area - Sanjaya, Mirza; Hermawan, Bambang; Apitule, Dorothea (Jurnal Ners, 2025)
Acute coronary syndrome, especially STEMI, is a major cause of mortality in Indonesia. Fibrinolytic reperfusion remains an important revascularization strategy, particularly in resource-limited settings. A 58-year-old male presented to the emergency department with severe chest pain radiating to the left arm and jaw for seven hours, unrelieved by rest. He also experienced diaphoresis and nausea. His history included 18 years of smoking and untreated hypertension. On examination, blood pressure was 176/111 mmHg with otherwise normal vital signs and no abnormal heart sounds. ECG revealed ST elevation in leads II, III, aVF, V5, and V6. The patient was diagnosed with inferior-apical STEMI, with possible posterior involvement, Killip I. Fibrinolytic therapy was administered with maximum dosage and duration. The key goal in STEMI management is achieving early and complete microvascular reperfusion. Fibrinolysis remains a practical alternative that reduces mortality when timely performed. Accurate diagnosis, appropriate therapy, and efficient referral systems are essential to improve outcomes, especially in archipelago regions with limited access to primary PCI.